2013
DOI: 10.1111/age.12019
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymorphisms in ovine prion protein gene

Abstract: The aim of this study was to identify the PRNP polymorphisms outside the standard codons 136, 154 and 171 in 1110 sheep with no clinical sign of scrapie from all 18 Turkish native sheep breeds and compare our results with published data on ovine PRNP polymorphism from other regions of the world. Among the 22 amino acid polymorphisms and three silent mutations, 10 were novel for ovine PRNP: p.Gly94Gly, p.Leu128Ile, p.Met132Leu, p.Ser135Arg, p.Met137Val, p.Asn146Lys, p.Arg159Arg, p.Tyr160Asn, p.Gln163His and p.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The remaining 18% of the goats carried at least one of the other PrP C variant and this frequency is not dissimilar to European populations (Goldmann 2008). Discounting the very common polymorphism S240P, on an average, one amino acid substitution was found for every 36 genotypes revealing that Turkish goats are at least as genetically varied in this locus as Turkish sheep, for which we genotyped on average 52 animals/substitution (Meydan et al 2013a).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The remaining 18% of the goats carried at least one of the other PrP C variant and this frequency is not dissimilar to European populations (Goldmann 2008). Discounting the very common polymorphism S240P, on an average, one amino acid substitution was found for every 36 genotypes revealing that Turkish goats are at least as genetically varied in this locus as Turkish sheep, for which we genotyped on average 52 animals/substitution (Meydan et al 2013a).…”
Section: Discussionmentioning
confidence: 82%
“…In Turkey, scrapie control breeding programmes have not been established for sheep and goats because there have not been any confirmed scrapie cases. Although, all Turkish native sheep breeds have been PRNP genotyped to evaluate the genetic risk for both classical and atypical scrapie (Meydan et al 2012(Meydan et al , 2013a, this is the first study to genotype PRNP in all Turkish native goat breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scrapie distribution in goats During the last years, genetic selection has been implemented in Europe and in the United States (Coseddu et al, 2007;Pongolini et al, 2009;Meydan et al, 2013).…”
Section: Scrapie Diagnosismentioning
confidence: 99%
“…In Mediterranean countries such as Italy, Greece and Spain ARQ/ARQ is a very frequent genotype detected in animals sick with scrapie (Coseddu et al, 2007;Nonno et al, 2003). However, many authors reported ARQ-associated SNPs related to scrapie-resistance (Acutis et al, 2004;Goldmann et al, 2005;Meydan et al, 2013;González et al, 2014).…”
Section: Introductionmentioning
confidence: 99%